Differentiating motor phenomena in tilt-induced syncope and convulsive seizures. (10th April 2018) - Shmuely, Sharon; Bauer, Prisca R.; van Zwet, Erik W.; van Dijk, J. Gert; Thijs, Roland D.
Abstract : Objective: We assessed motor phenomena in syncope and convulsive seizures to aid differential diagnosis and understand the pathophysiologic correlates. Methods: We studied video-EEG recordings of tilt-induced syncope and convulsive seizures in participants aged 15 years and older. Syncope was defined as (1) loss of consciousness (video-assessed), (2) circulatory changes (accelerating blood pressure decrease with or without bradycardia/asystole), and (3) EEG changes ("slow" or "slow-flat-slow"). We assessed myoclonic jerks and tonic postures of the arms and noted time of occurrence, laterality, synchrony, and rhythmicity (mean consecutive differences of interclonic intervals). Results: Video-EEG records of 65 syncope cases and 50 convulsive seizures were included. In syncope, postures occurred in 42 cases (65%) and jerks in 33 (51%). Fewer jerks occurred in syncope (median 2, range 1–19) compared to convulsive seizures (median 48, range 20–191; p < 0.001). Jerks were more rhythmic in seizures compared to syncope ( p < 0.001). Atonia was seen in all syncope cases, while this was not observed in any seizure. Jerks predominantly occurred during the slow and postures during the flat EEG phase. Conclusions: Jerks and tonic postures were common in syncope, but semiology differed from convulsive seizures. The lack of overlap in the number of jerks suggests that less than 10 indicates syncope and more than 20 a convulsive seizure: the "10/20 rule." Loss of tone strongly favors syncope. The EEG correlates imply that jerks in syncope are likely of cortical origin, whereas tonic postures may result from brainstem disinhibition.